Psyllaphorura jiangsuensis sp. nov. from China (Collembola: Onychiuridae) - Yan, Haijuan; Huang, Cheng; Chen, Jian-Xiu (Zootaxa, 2007)
The genus Psyllaphorura is reported from China for the first time. A new species, Psyllaphorura jiangsuensis sp. n. as the eighth species of the genus, is described from Nanjing, Southeast China. It is most similar to the Russian species Psyllaphorura martynovae (Stebaeva, 1985) in many respects. However, it can be distinguished from the latter by number of vesicles in the postantennal organ, number of setae on ventral tube, length ratio of unguiculus to unguis, absence of unguiculus basal lamella and maximum body length. A key to all of the species of Psyllaphorura is provided.